Fatigue-induced changes in knee kinematics and muscle forces in professional handball-specific task - Bedo, B. L.S.; Catelli, D. S.; Pereira, D. R.; Assis, R. D.; Santiago, P. R. P.; Lamontagne, M. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study investigated the impact of fatigue on knee kinematics and muscle forces in female handball athletes performing sidestep-cutting manoeuvres. Twenty athletes completed six trials, each divided equally before and after a handball-specific fatigue protocol. Kinematic and kinect data were gathered using an infrared motion capture system and a force plate. Analysis was performed with OpenSim 3.3. The results were compared using statistical parametric mapping. They indicated significant fatigue-related decreases in knee flexion during the early stance phase, reduced activity in the vastus intermedius and medialis muscles. Therefore, the findings indorms the design of programs focused on improving muscle endurance; however, there is still no conclusive evidence linking fatigue to an increased risk of knee load.